Association of Primary Cesarean Delivery Rate With Dissemination of Nurse-Specific Cesarean Delivery Rates. Issue 4 (7th October 2022) - Greene, Naomi H.; Schwartz, Nicole; Gregory, Kimberly D.
Abstract : Dissemination of nurse-specific cesarean delivery rates was associated with a reduction in the hospital's primary cesarean delivery rate. Abstract : Strategies to safely reduce the rate of nulliparous, term, singleton, vertex (NTSV) cesarean deliveries have thus far largely ignored the contribution that labor and delivery nurses make to the delivery mode. We used a recently developed method to calculate nurse-specific cesarean delivery rates and provide these to labor and delivery nursing leadership, who shared the rates with labor and delivery nurses beginning in September 2020. We performed a 3-year interrupted time series analysis comparing our NTSV cesarean delivery rates before and after nurse-specific rates were released. On release of nurse-specific rates, our labor and delivery unit's NTSV cesarean delivery rate declined from 25.7% to 22.0%. Further work to find strategies to sustain nurse engagement is warranted.